Spatial Dynamics Model of Land Availability and Population Growth Prediction in Bengkulu City - Della Ayu Lestari; Dewi Susiloningtyas; Supriatna Supriatna (Indonesian Journal of Geography, 2020)
Bengkulu City is the center for almost all activities and has a high population growth rate. Because of the high population growth rate, human needs for space and land will increase. Land availability will continue to decline, while it cannot increase the existing area. This will impact the carrying capacity of the environment, so it needs predictions for land availability. This study used a spatial dynamics model which is an analysis of the dynamic system model and the suitability of the built-up area. The carrying capacity to reach excellent quality when the length of the built-up area is 30-70% of the total area that can be used. The results showed that the built-up area will reach 70% in 2030, which means it will exceed the environmental carrying capacity threshold. The results showed there were differences between the distribution patterns of built-up area in the spatial dynamics model and Spatial Planning Bengkulu City in 2032 at Kampung Melayu Subdistrict, Selebar Subdistrict, Singaran Pati Subdistrict, and Sungai Serut Subdistrict.